Tumor-associated neutrophils in breast cancer: an angel or a devil? - Wen, Siyuan; Feng, Tianli; Fan, Yu (Frontiers in Immunology, 2025)
Breast cancer is the most common malignant tumor in women, ranking first globally in both incidence and mortality rates among female malignancies, posing a severe threat to women’s physical and mental health. Neutrophils are recognized as the first line of host defense against pathogens and exert beneficial effects in the body. However, emerging evidence has demonstrated that tumor-associated neutrophils (TANs) exhibit a dual role in breast cancer progression and prognosis. Therefore, elucidating their molecular mechanisms may provide novel insights for targeted therapies, potentially improving clinical outcomes for breast cancer patients. This review summarizes the interplay between TANs and breast cancer, their underlying mechanisms, and their potential as immunotherapeutic targets.